2020
DOI: 10.1038/s43247-020-00039-w
|View full text |Cite
|
Sign up to set email alerts
|

Significant stream chemistry response to temperature variations in a high-elevation mountain watershed

Abstract: High-elevation mountain regions, central to global freshwater supply, are experiencing more rapid warming than low-elevation locations. High-elevation streams are therefore potentially critical indicators for earth system and water chemistry response to warming. Here we present concerted hydroclimatic and biogeochemical data from Coal Creek, Colorado in the central Rocky Mountains at elevations of 2700 to 3700 m, where air temperatures have increased by about 2 °C since 1980. We analyzed water chemistry every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 75 publications
2
32
0
Order By: Relevance
“…This is consistent with field observations that soil CO 2 production rate and efflux may increase with rainfall in grassland and forest ecosystems (Harper et al, 2005;Patrick et al, 2007;Wu et al, 2011;Vargas et al, 2012;Jiang et al, 2013). For example, Zhou et al (2009) documented soil CO 2 production rates increasing from 3.2 to 63.0 mol/m 2 /a when the annual precipitation increased from 400 to 1200 mm. Wu et al (2011) showed that increasing precipitation from 5 to 2148 mm enhanced soil respiration by 40 % and that a global increase of 2 mm precipitation per decade may lead to an increase of 3.8 mol/m 2 /a for soil CO 2 production.…”
Section: Reactionssupporting
confidence: 89%
“…This is consistent with field observations that soil CO 2 production rate and efflux may increase with rainfall in grassland and forest ecosystems (Harper et al, 2005;Patrick et al, 2007;Wu et al, 2011;Vargas et al, 2012;Jiang et al, 2013). For example, Zhou et al (2009) documented soil CO 2 production rates increasing from 3.2 to 63.0 mol/m 2 /a when the annual precipitation increased from 400 to 1200 mm. Wu et al (2011) showed that increasing precipitation from 5 to 2148 mm enhanced soil respiration by 40 % and that a global increase of 2 mm precipitation per decade may lead to an increase of 3.8 mol/m 2 /a for soil CO 2 production.…”
Section: Reactionssupporting
confidence: 89%
“…The concentrations are at levels commonly observed in natural systems. For example, Al can reach as high as tens of μmol/L that is, within the high end of observed concentration ranges (Herndon et al., 2015; Zhi et al., 2020).…”
Section: Resultsmentioning
confidence: 86%
“…It is possible that chemostatic patterns from earlier data result from infrequent (often bimonthly) data mostly in low and intermediate flow regimes. Recent, more frequently sampled stream chemistry data rarely show chemostatic patterns (Knapp et al., 2020; Torres et al., 2015; Zhi et al., 2020). At minute and hourly time scales, highly resolved temporal solute data have demonstrated highly dynamic, contrasting CQ patterns in events of different size and antecedent conditions (Burns et al., 2019; Duncan et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Q) relationships of solutes at stream and river outlets. Similar C-Q relationships have been observed for some solutes across watersheds under distinct geological and climatic conditions (Godsey et al, 2009;Basu et al, 2010;Moatar et al, 2017;Zarnetske et al, 2018;Godsey et al, 2019), whereas different solutes have shown contrasting patterns in the same watershed (Miller et al, 2017;Herndon et al, 2015;Musolff et al, 2015;Stewart et al, 2021;Zhi et al, 2020b). A general theory that can explain contrasting C-Q observations (e.g., flushing vs. dilution behaviors) under diverse watershed characteristics and external conditions remains elusive.…”
Section: Introductionmentioning
confidence: 89%